Improving anaerobic digestion of a cellulosic waste via routine bioaugmentation with cellulolytic microorganisms. (August 2015) - Martin-Ryals, Ana; Schideman, Lance; Li, Peng; Wilkinson, Henry; Wagner, Richard
Highlights: Anaerobic digestion of a cellulosic waste with routine bioaugmentation was studied. A cellulolytic bioculture mix was used to target and sustain improved hydrolysis. Routine bioaugmentation out performed typical one-time bioaugmentation. Routine bioaugmentation increased hydrolysis, acetic acid levels, and methane yield. Long-term lab-scale operation showed sustained benefits with routine bioaugmentation. Abstract: This study investigated routine bioaugmentation in the acid-phase of a two-phase anaerobic digestion (AD) process treating a largely cellulosic waste material generated from sweet corn processing. A proprietary cellulolytic bioculture was used for bioaugmentation with the aim of increasing substrate hydrolysis to improve overall methanogenic efficiency. In a sequencing batch experiment routine bioaugmentation achieved significantly greater soluble chemical oxygen demand (sCOD) generation (+25%) and methane production (+15%) compared to one-time bioaugmentation. In a continuous bench-scale system, routine bioaugmentation increased acid-phase sCOD by 29–68% and acetic acid concentrations by 31–34%. This benefit to hydrolysis and acetogenesis subsequently led to sustained increase in methane production (+56%) compared to non-bioaugmentation. A cursory economic analysis indicated that routine bioaugmentation could improve the economics of corn waste AD by $27–$34/dry tonne of waste. Overall, routine bioaugmentation showed significant promise for improving AD of corn waste by achieving sustained increases in substrate hydrolysis and methane production.